Diversity in Aβ deposit morphology and secondary proteome insolubility across models of Alzheimer-type amyloidosis - Guilian Xu (Acta Neuropathologica Communications, 2020)
Abstract A hallmark pathology of Alzheimer’s disease (AD) is the formation of amyloid β (Aβ) deposits that exhibit diverse localization and morphologies, ranging from diffuse to cored-neuritic deposits in brain parenchyma, with cerebral vascular deposition in leptomeningeal and parenchymal compartments. Most AD brains exhibit the full spectrum of pathologic Aβ morphologies. In the course of studies to model AD amyloidosis, we have generated multiple transgenic mouse models that vary in the nature of the transgene constructs that are expressed; including the species origin of Aβ peptides, the levels and length of Aβ that is deposited, and whether mutant presenilin 1 (PS1) is co-expressed. These models recapitulate features of human AD amyloidosis, but interestingly some models can produce pathology in which one type of Aβ morphology dominates. In prior studies of mice that primarily develop cored-neuritic deposits, we determined that Aβ deposition is associated with changes in cytosolic protein solubility in which a subset of proteins become detergent-insoluble, indicative of secondary proteome instability. Here, we survey changes in cytosolic protein solubility across seven different transgenic mouse models that exhibit a range of Aβ deposit morphologies. We find a surprisingly diverse range of changes in proteome solubility across these models. Mice that deposit human Aβ40 and Aβ42 in cored-neuritic plaques had the most robust changes in proteome solubility. Insoluble cytosolic proteins were also detected in the brains of mice that develop diffuse Aβ42 deposits but to a lesser extent. Notably, mice with cored deposits containing only Aβ42 had relatively few proteins that became detergent-insoluble. Our data provide new insight into the diversity of biological effects that can be attributed to different types of Aβ pathology and support the view that fibrillar cored-neuritic plaque pathology is the more disruptive Aβ pathology in the Alzheimer’s cascade.